Pengaruh Green Intellectual Capital, Green Human Resource Management terhadap Evironmental Performance yang Dimediasi oleh Green Innovation pada Karyawan Perusahaan Manufaktur di Jakarta Barat - Wijaya, Sanjuan Erlin; Emilisa, Netania; Ardita, Siska Juni; Ramadhan, Muhammad Rangga Mardhika (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the influence of Green Intellectual Capital and Green Human Resource Management on Environmental Performance, mediated by Green Innovation, among employees of manufacturing companies in West Jakarta. Based on descriptive analysis results, it was found that manufacturing employees agree with the existence of Green Intellectual Capital because they care about the environment. They also agree with Green Human Resource Management, feeling that the company sets environmentally friendly goals for employees. Green Innovation is also approved by employees, indicating that the company often emphasizes the development of environmentally friendly products and the collection of information about environmental innovation trends. Environmental Performance is also agreed upon, with employees feeling that environmental management efforts have significantly reduced production waste. Hypothesis testing results show a significant positive influence of Green Intellectual Capital on Green Innovation, as well as on Environmental Performance. Additionally, there is a significant positive influence of Green Human Resource Management on Green Innovation and Environmental Performance. Green Innovation is also found to have a significant positive influence on Environmental Performance and mediates the significant positive influence of Green Intellectual Capital and Green Human Resource Management on Environmental Performance. These findings provide important insights into the importance of Green Intellectual Capital, Green Human Resource Management, and Green Innovation in improving environmental performance in manufacturing companies. Keywords: Green Intellectual Capital, Green Human Resource Management, Environmental Performance, Green Innovation, Manufacturing Employees, West Jakarta.